Impact of Composting and Vermicomposting of Three Types of Animal Manure on the Dynamics of Macronutrients Nitrogen, Phosphorus and Potassium - Issa Ale Ndiaye; Amadou Balde; Oumar Seydi; Etienne Tendeng; Serigne Sylla; Karamoko Diarra (European Scientific Journal, ESJ, 2025)
The management of animal manure remains a major environmental challenge, sparking growing interest in valorization methods such as composting and vermicomposting. However, the efficiency of the composting method largely depends on the type of organic substrate used. This study aims to evaluate the impact of composting methods on the final concentrations of nitrogen (N), phosphorus (P), and potassium (K) in three types of animal manure. Three types of animal manure (horse dung, cow dung, and poultry droppings) underwent a five-week pre-composting phase, followed by seven weeks of vermicomposting. Two earthworm species, Eudrilus eugeniae and Eisenia fetida, were used in the vermicomposting process. Soluble concentrations of N, P, and K were measured at the end of the composting and vermicomposting processes, and the impact of composting method on nutrient dynamics (N, P, K) in the soil was assessed both before transplanting and after harvesting a lettuce crop. During composting, cow dung and poultry droppings showed similar nitrogen levels (0.3 kg N/ha), which were significantly higher than those of horse manure (0.2 kg N/ha). Poultry droppings displayed the highest phosphorus (0.18 kg P/ha) and potassium (0.25 kg K/ha) concentrations, compared to cow dung (0.12 kg P/ha, 0.1 kg K/ha) and horse manure (0.1 kg P/ha, 0.1 kg K/ha). In vermicomposting, nutrient differences between manure types were less pronounced. Nitrogen levels were higher in compost than in vermicompost for poultry droppings (0.38 kg N/ha vs. 0.33 kg N/ha), while P and K levels remained similar between the two processes for cow dung. This study highlights the differential impact of composting and vermicomposting on the nutrient content of organic amendments. Composting appears to be more effective for poultry droppings, while vermicomposting yields comparable nutrient levels for horse and cow manure. These findings provide valuable insights for optimizing organic waste recycling to enhance soil fertility.